Report of the Backward Classes Commission First Part Volumes I and II 1980 - Planning Commission (Planning Commission, 1984)
The 1980 Report of the Backward Classes Commission (Mandal Commission) presents a comprehensive analysis of the social, educational, and economic backwardness of Other Backward Classes (OBCs) in India. Chaired by B.P. Mandal, the Commission examined historical injustices, caste-based discrimination, and underrepresentation in government services, highlighting systemic inequities that perpetuate disadvantage. Utilizing surveys, questionnaires, and public evidence, the report emphasized the need for targeted interventions, including reservation policies in education and employment, expansion of vocational and adult education programs, and financial empowerment through dedicated institutions and cooperatives. It also recommended structural reforms, such as land redistribution and enhanced state-level coordination, to break entrenched socio-economic hierarchies. The report underscores the interplay of caste dynamics and political mobilization, advocating for policies that ensure equitable representation, promote social justice, and integrate OBCs into the broader socio-economic framework of India.
Government of India
Government of India
Keywords: Backward Classes; OBC Welfare; Mandal Commission; Social Justice; Reservation Policies; Educational Backwardness; Socio-Economic Survey; Employment Disparities; Caste Dynamics; Government Policy; Affirmative Action; Structural Reforms